Detection of asymptomatic Solanum lycopersicum L. plants infected with Fusarium oxysporum using reflectance VIS spectroscopy - Marín-Ortiz, Juan Carlos; Hoyos-Carvajal, Lilliana María; Botero Fernandez, Veronica (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2018)
Asymptomatic plants are reservoirs of pathogens because they can remain infected most of the development cycle, becoming a source of contamination for the rest of the crop. The objective of this study was to evaluate a method of detection and discrimination of two F. oxysporum isolates on tomato plants using reflectance spectroscopy in the VIS region. The incidence of the fungal isolate from the purple passion fruit plants (F05) was greater than that observed in the strain isolated from the tomato plant (F07), with values of 60.0% at 11 days and 81.8% at 22 days; the incidence present in the plants with strain F07 was 30.0% and 64.3% in the evaluated period. The F05 strain showed better grouping in both periods of time, both in the Principal Component Analysis and Linear Discriminant Analysis, than the controls, as did the F07 strain. These results suggest that reflectance spectroscopy in the VIS is a sensitive and reliable method that may be suitable for early diagnosis of plant diseases.